2012
DOI: 10.1523/jneurosci.6331-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

KIF21A-Mediated Axonal Transport and Selective Endocytosis Underlie the Polarized Targeting of NCKX2

Abstract: We have previously shown that K ϩ -dependent Na ϩ /Ca 2ϩ exchanger (NCKX) is a major calcium clearance mechanism at the large axon terminals of central neurons, whereas their somata display little NCKX activity. We investigated mechanisms underlying the axonal polarization of NCKX2 in rat hippocampal neurons. We identified NCKX2 as the first neuron-specific cargo molecule of kinesin family member 21A (KIF21A). The intracellular loop of NCKX2 specifically interacted with the WD-40 repeats, a putative cargo-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
(78 reference statements)
4
21
0
Order By: Relevance
“…In vitro, the KIF21A motor domain behaves similarly to that of Xklp1 – it reduces the MT growth rate and suppresses catastrophes (van der Vaart et al, 2013). There are also indications that in addition to controlling MT dynamics, KIF21A plays a role in membrane transport (Lee et al, 2012). All CFEOM1-associated mutations in KIF21A localize either to the motor domain or to a predicted short coiled-coil domain in the stalk region of the molecule, and each of them prevents the autoinhibitory interaction between these two elements (Bianchi et al, 2016; Cheng et al, 2014; van der Vaart et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, the KIF21A motor domain behaves similarly to that of Xklp1 – it reduces the MT growth rate and suppresses catastrophes (van der Vaart et al, 2013). There are also indications that in addition to controlling MT dynamics, KIF21A plays a role in membrane transport (Lee et al, 2012). All CFEOM1-associated mutations in KIF21A localize either to the motor domain or to a predicted short coiled-coil domain in the stalk region of the molecule, and each of them prevents the autoinhibitory interaction between these two elements (Bianchi et al, 2016; Cheng et al, 2014; van der Vaart et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that dynamin-1-mediated endocytosis is involved in the low surface expression of NCKX2 in the somatodendritic region (Lee et al, 2012). Dynamin-1 is one of the key players in clathrin-mediated endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, based on studies of the decay phase of calcium transients, we have reported that NCKX activity is the major CCM at axon terminals but is not detectable in somatodendritic regions of central neurons (Kim et al, 2003, 2005; Lee et al, 2009). Furthermore, we have shown that the surface expression of NCKX2 is polarized to the axonal compartment (Lee et al, 2012) in cultured hippocampal neurons. This view is in disagreement with other studies, which showed the direct recording of NCKX current or Ca 2+ -influx via the reverse mode of NCKX in the somata of cortical neurons (Kiedrowski et al, 2004; Cuomo et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mutations in the KIF21A stalk region have been shown to be the underlying cause of congenital fibrosis of the extraocular muscle type 1 (CFEOM1) (Yamada et al, 2003), which is associated with defects in the oculomotor nerve and results in an inability to move or raise the eyes. A recent study showed that knockdown of KIF21A causes the dysregulation of Ca 2+ at axonal boutons owing to inhibited transport of NCKX2, a K + -dependent Na + -exchanger that is involved in Ca 2+ clearance in the large axon terminals of central neurons (Lee et al, 2012). Moreover, a mutation in KIF1B-b, a kinesin-3 family member, was identified in CMT2 patients (Zhao et al, 2001).…”
Section: Journal Of Cell Sciencementioning
confidence: 99%